The use of Korean and Indonesian downgraders in Miss Granny and Sweet 20: A comparative study - Rosyadi, Alfiana Amrin (Universitas Pendidikan Indonesia (UPI), 2024)
Politeness strategies reflect a deep-seated cultural value of respect and consideration for others' feelings, which significantly influences how individuals communicate in burdensome situations. This research aims to find out the different usage and forms of downgraders in Korean and Indonesian by analysing the same situations in drama titled Miss Granny and Sweet 20. Downgraders commonly appear in face threathening situation for reducing the burden of speaker. By thus, downgraders can be seen as a communication tool that language learners have to acquired. But since the Korean and Indonesian downgraders’s forms are different, the learners of both language likely to have difficulty to use. This research used qualitative method by examining the downgraders in ‘Miss Granny’ and ‘Sweet 20’. The collected data regarding downgraders were analyzed and compared based on each situation that included face threatening situation. The results showed that both language used downgraders in four situations such as asking for information, asking for request, giving advice and rejection. However since the form of downgraders are different, this research stressed the important of the teaching of downgraders in language learning classroom.